The Urgency of Presidential Regulation No. 21 of 2024 in the Context of Social Assistance and Online Gambling in Indonesia - Nur Ayu; Tetty Melina Lubis; Arief Fahmi Lubis (West Science Law and Human Rights, 2024)
This study examines the urgency of Presidential Regulation No. 21 of 2024 in addressing the dual issues of social assistance distribution and online gambling in Indonesia through a normative juridical analysis. The regulation aims to enhance the efficiency and transparency of social assistance programs while implementing stringent measures to control the proliferation of online gambling. Key provisions include the establishment of a centralized database, digital payment systems, regular audits, and strict licensing requirements for online gambling platforms. The analysis reveals that these measures are well-aligned with existing laws and have the potential to significantly improve social welfare and mitigate the negative impacts of online gambling. However, successful implementation will require overcoming challenges such as bureaucratic resistance and technological infrastructure needs. The study underscores the regulation's pivotal role in promoting social welfare and provides insights for policymakers to further strengthen regulatory frameworks in these areas.